PEMBELAJARAN PENDIDIKAN INKLUSI PADA SEKOLAH DASAR - Kurniawati, Lia (EDUTECH, 2017)
Abstract. The learning process and the handling of Children with Special Needs (ABK) grade inclusions pinned to the classroom teacher in several schools without teacher inclusion Spe-cial Assistants (GPK) the background for this thesis. Theoretically GPK still needed to be able to assist the process of Teaching and Learning Activities (KBM) and according to researchers it will have implications for the management of classroom learning the handling of children with special needs and other students joined in the inclusive classroom. Special Advisors Teacher procurement program has not been met and this is an obstacle. As a first step to determine the problem, the au-thors examined the inclusive learning management with or without Teacher Special Assistants (GPK) in order to improve the service quality of education both in process and outcome. The im-plementation are not of cooperation team of child psychologists, pediatricians, neurologists, and psychologists who can contribute greatly to the effectiveness of teaching children with special needs. From the findings of the researchers in the field can provide recommendations that the live-liness of the school component can be improved by following IHT or KKT program organized by the Department of Education so that the provincial level without any GPK implementation of inclu-sive education learning can be run in accordance with national education goals.Keywords : Inclusive, Learning, Education, Teacher, GPKAbstrak. Proses pembelajaran dan penanganan Anak Berkebutuhan Khusus (ABK) kelas inklusi ditumpukan kepada guru kelas pada beberapa sekolah inklusi tanpa Guru Pendamping Khu-sus (GPK) yang melatar belakangi penelitian tesis ini. Secara teoritis GPK tetap dibutuhkan untuk dapat membantu proses Kegiatan Belajar Mengajar (KBM) dan menurut peneliti hal ini akan ber-implikasi pada manajemen pembelajaran di kelas terhadap penanganan anak berkebutuhan khusus maupun siswa lainnya yang tergabung dalam kelas inklusif. Pengadaan Guru Pembimbing Khusus belum terpenuhi dan hal ini merupakan kendala. Sebagai langkah awal untuk mengetahui masalah tersebut, penulis meneliti manajemen pembelajaran inklusif dengan atau tanpa Guru Pendamping Khusus (GPK) guna meningkatkan layanan mutu pendidikan baik proses maupun hasil. belum ter-laksananya kerjasama tim yang terdiri dari para ahli psikologi anak, dokter anak, dokter neurologi, dan psikolog yang dapat memberikan kontribusi yang besar terhadap efektifitas pembelajaran Anak Berkebutuhan Khusus. Dari hasil temuan dilapangan peneliti dapat memberikan rekomendasi bah-wa keaktifan komponen sekolah dapat ditingkatkan dengan mengikuti IHT atau program KKT yang diselenggarakan oleh Dinas Pendidikan tingkat Provinsi sehingga tanpa GPK pun penyeleng-garaan pembelajaran pendidikan inklusif dapat berjalan sesuai dengan tujuan pendidikan nasional.Kata Kunci : Inklusi, Pembelajaran, Pendidikan, Guru, GPK